INTERCONNECTION OF PHOSPHATE-CALCIUM REGIME OF RESERVOIRS WITH THEIR BIOPRODUCTIVITY (REVIEW) - Solomatina, Valentyna; Pinkina, Tetiana; Svitelskyi, Mykola; Matkovska, Svitlana; Ishchuk, Oksana; Fediuchka, Mykola (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
The data on the content of calcium and phosphorus in continental waters of different geological zones of Ukraine is summarized, since these elements determine the course of many physical and chemical processes in water bodies and affect their bioproductivity. Calcium and phosphorus are extremely important structural elements of all living systems that play an important role in regulating the processes occurring inside the reservoirs, which are of great importance in determining the trophy of water bodies. One of the criteria for assessing the possible role of mineral salts in the life of hydrobionts is the establishment of the relationship between the total mineralization of water, its ionic composition, the abundance and biomass of individual aquatic organisms. Changes in the content of calcium and phosphorus in water can have both direct and indirect effects through planktonic and benthic fodder organisms, on the species composition and number of fish living in marine and continental waters. There is evidence that there is a correlation between the change in the ratio of calcium, phosphorus and other elements in water to the species composition and number of fish. The chemical state of surface water, including the content of calcium and phosphorus in them, is marked by a large variety due to geological and soil conditions and anthropogenic influences. Calcium and phosphorus are extremely important structural elements of all living systems, which play an essential role in regulating processes occurring inside the reservoirs, which are of great importance in determining the trophy of reservoirs. Increasing anthropogenic eutrophication of continental reservoirs, increasing the content of calcium phosphates and other minerals significantly affects the development of individual forms of hydrobionts. In connection with an increase in the content of phosphates and other biogenic elements in many reservoirs, the biomass of phytoplankton has increased, the number of individual forms of malacafauna and ichthyofauna has changed. Therefore, the role of phosphorus and calcium in the activity of hydrobionts as the most important plastic elements that take part in the regulation of the main metabolic processes occurring at different levels of the organization of living systems is of particular importance. One of the tasks set before hydrobiological science is to increase the productivity of internal reservoirs, including fish productivity. Solving this problem requires the further development of research into the mechanisms of adaptation of fish to environmental factors of the water environment. An important aspect of this question is the study of phosphoric-calcium metabolism in hydrobionts, in particular in fish, because it is closely related to bioenergetic, biosynthetic and other processes in the body. It is established that in the mechanism of animal adaptation the leading role belongs to the energy metabolism, in particular, the metabolism of macroergic phosphorus compounds. Calcium and phosphorus play an important role in the life of reservoirs, determining the course of many physical and chemical processes and affecting their bioproductivity. The content of these elements in the waters of different reservoirs varies widely. It is known that in atmospheric precipitation entering the water body, there is practically no calcium and contains a small amount of phosphorus. As a result of the interaction of atmospheric precipitation with geological rocks and soils, water is enriched with various organic and mineral substances, in particular calcium and phosphorus. This can be explained by the fact that in each geochemical zone there are water with a chemical-specific specific to each region.